Exploring the Drivers of Green Skincare Purchases: Income, Norms, Trust, Knowledge and Attitude - Alifah Nafisatul Khoridah; Nabila Na'ma Aisa; Fauziyah Nur Jamal (SENTRALISASI, 2026)
This research aims to analyze the influence of income, subjective norms, social media, financial literacy, green trust, environmental knowledge, and environmental attitude on green skincare purchase decisions among Generation Z in Indonesia, as well as to examine the mediating role of environmental attitude. This study is quantitative and uses an online survey method, involving 358 Generation Z respondents who use green skincare products. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that subjective norms, social media, financial literacy, green trust, environmental knowledge, and environmental attitude have a significant positive influence on green skincare purchase decisions, while income does not. In addition, environmental attitude was found to mediate the relationship between environmental knowledge and purchase decisions. This study demonstrates that sustainable consumption behavior among Generation Z is more strongly influenced by social, psychological, and sustainability value factors than by economic factors.